Makna Syukur dalam Al-Qur’an dan Relevansinya bagi Kehidupan Modern - Nikhlah Ziyadaturrohmah; Syafiin Mansur; Wita Wita; Muhamad Zaky Hamdie; Maelina Putri Maratu Sholihah (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
The meaning of gratitude according to the perspective of the Qur'an and its relationship to modern human life which is influenced by technological advances, materialistic lifestyles, and social pressures. In the view of the Qur'an, gratitude is not merely expressed through words, but involves the awareness of the heart, verbal words, and real actions as a form of recognition of the blessings given by Allah SWT. Gratitude also functions as a reflection of faith that combines spiritual, moral, and social elements. In the context of modern life, the meaning of gratitude has shifted due to consumptive lifestyles and the culture of seeking recognition on social media, which has an impact on decreasing feelings of satisfaction and inner peace. This study uses a qualitative approach with a library research method through a review of the verses of the Qur'an, tafsir books, and various relevant academic literature. The results of the study show that the teachings of gratitude in the Qur'an play an important role in maintaining spiritual, emotional, and spiritual balance in the midst of modern life. The application of an attitude of gratitude has been proven to improve mental health, strengthen social relationships, and reduce materialistic tendencies. Furthermore, the value of gratitude can serve as a moral guideline for Generation Alpha, enabling them to balance technological advancement with spiritual life. Overall, the teachings of gratitude in the Quran remain universally relevant, not only as a religious obligation but also as a spiritual and social necessity that can bring happiness, serenity, and meaning to life amidst the dynamics of the digital age.